1991
DOI: 10.1001/archderm.1991.01680050087009
|View full text |Cite
|
Sign up to set email alerts
|

Immunoblot Assay as an Aid to the Diagnoses of Unclassified Cases of Pemphigus

Abstract: With use of an immunoblot assay for both the normal human epidermal extracts and the bovine desmosome preparation, we investigated sera from 18 patients with pemphigus, who exhibited atypical clinical or histologic features and whose diagnoses were difficult to identify. Four sera yielded a 130-kd protein band in the epidermal extracts, which is characteristic of pemphigus vulgaris. A 150-kd protein was identified by nine sera in the epidermal extracts and/or the desmosome preparation, which is known as a pemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 21 publications
0
19
1
2
Order By: Relevance
“…However, this does not negate the fact that the WB method reveals the majority of pemphigus antigen determinants. Indeed, a couple of studies 31,32 have found a good correlation between IIF titres and immunoblotting reactivity.…”
Section: Discussionmentioning
confidence: 98%
“…However, this does not negate the fact that the WB method reveals the majority of pemphigus antigen determinants. Indeed, a couple of studies 31,32 have found a good correlation between IIF titres and immunoblotting reactivity.…”
Section: Discussionmentioning
confidence: 98%
“…Transition between the main subtypes of pemphigus, pemphigus vulgaris (PV) and pemphigus foliaceus (PF), is rarely reported in the literature. Nevertheless when such a transition does occur, a change from PV to PF is more common 1–4 than a change from PF to PV 2,4 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…The PF antigen is now clearly established as a 165-kDa protein named desmoglein I which is an essential component of the desmosome [6]. The PV target antigen has been identified by immunoprecipitation [5] as well as by Western immunoblotting on bovine tongue [14] or skin extract [18] and is a protein of molecular weight 130 kDa. In addition, molecular biology has shown that the PV antigen and desmoglein I are two different members of the desmoglein subfamily of desmosomal cadherins which are calcium-dependent proteins [19].…”
Section: Discussionmentioning
confidence: 99%